PERANCANGAN BASIS DATA PADA SISTEM UTANG PIUTANG STUDI KASUS PT. RAPITAMA INTERTECH BUANA - Fadillah, Rama Afan; Souhoka, Bagas Adiansyah; Runtuwene, Faithly Jabez Jefune; Meldiansah, Reza; Fathan, Muhammad (Jurnal Ilmiah Sistem Informasi, 2023)
PT. Rapitama Intertech Buana is a company that operates in the interior and exterior sectors. This company has several customers who carry out sales transactions in installments. To manage accounts payable from these customers, the company uses a manual system. The manual system currently used has several shortcomings, such as the accounts payable and receivable management process which is inefficient and takes a long time. Therefore, the research team reached an agreement, namely by developing a better and more efficient transaction recording system so that there was no need to involve many parties when transactions between clients and companies occurred. By developing that transaction recording system, it is hoped that the system can overcome the problems in the company under study